Aspects of Current Management of Distal Radius Fractures in the Elderly Individuals - Rohit Arora MD (Geriatric Orthopaedic Surgery & Rehabilitation, 2011)
Diatal radius fractures (DRFs) are typical fractures of relatively fit persons with osteoporotic bone who remain active into older age. Traditionally, DRFs in older patients have been treated with closed reduction and cast immobilization. Considering the increasing life expectancy of the elderly population, appropriate management of these fractures is of growing importance. Decision making for surgical or nonsurgical approach to osteoporotic DRFs is difficult. These decisions are often made based on the data from treatments of much younger patients. The current literature concerning the treatment of DRFs in the elderly individuals is more controversial. Some investigators have recommended open reduction internal fixation (ORIF) as treatment for unstable DRFs in older patients, while others have suggested that elderly patients should be treated nonsurgically even if there is an unstable fracture situation because fracture reduction is not associated with functional outcomes as in younger patients. This article reviews the different treatment options for DRFs in the elderly individuals reported in the recent literature.